Discurso poético y semiosfera urbana: miradas sobre La Habana y Buenos Aires a comienzos del siglo XXI - María Lucía Puppo (Nuevo mundo - Mundos Nuevos, 2009)
This paper focuses on a comparative analysis of contemporary urban space semiosis in both La Quinta de los Molinos (2000) written by the Cuban writer Nancy Morejón, and Solos y solas (2005) by the Argentinean poet Tamara Kamenszain. Taking as departure point the concept of “semiosphere” created by Iuri Lotman, this article confronts some features of the “semiotic personality” of La Havana and Buenos Aires as portrayed in the chosen corpus.